A Systematic Literature Review of Malcolm Baldrige National Quality Award (MBNQA) in Organization - Ojakma Sihar Panaili Tumanggor; Humiras Hardi Purba (Proceeding Mercu Buana Conference on Industrial Engineering, 2019)
In today's free-market economy, increasingly fierce market competition for organizational goals requires all parties to be able to produce the best products or services in; winning the competition is the main responsibility of management. The National Quality Malcolm Baldrige (MBNQA) for evaluating performance in all organizations, which is used to evaluate performance in organizations. Successful application of Malcolm Baldrige's Quality Framework criteria in organizations. The Malcolm Baldrige National Quality Award (MBNQA) is a method to improve overall organizational performance and continuously (continuous improvement) by using measurements and providing feedback on overall organizational performance in providing quality products and services. The MBNQA not only can be implemented in the industry but spread to several sectors such as hospital service, hotel, education, public service, etc. Implementing of MBNQA in Healthcare increases management quality achieved. Workforce Focus 74.3%, Operation Focus 75.6%, Results 75,6%, have  a significant relationship with sub-category two to sub-category seven MBCfPE as a variable. The software system can produce an estimated score for each analysis approach Approach, Deployment, Learning and Integration (ADLI) for each requirement successive values of 91.73% and 86.79%. the threat to service with 56.11% for FKTP ISO and 64.68% for FKTP.